Knowledge and Practices Regarding Self-Management of Minor Ailments among Pregnant Mothers - Samara, Suduweli Koonge Sashanika Nishadi; Mohamed, Fathima Farhana Habeeb; Madushanka, Kalanchi Mahadurage Shalitha; Gnanaselvam, Kisokanth (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: